Implementing evidence-informed deliberative processes in health technology assessment: a low income country perspective. (16th January 2020) - Kapiriri, Lydia; Baltussen, Rob; Oortwijn, Wija
Abstract: The purpose of this paper is to discuss the potential feasibility and utility of evidence-informed deliberative processes (EPDs) in low income country (LIC) contexts. EDPs are implemented in high and middle income countries and thought to improve the quality, consistency, and transparency of decisions informed by health technology assessment (HTA). Together these would ultimately improve the legitimacy of any decision making process. We argue—based on our previous work and in light of the priority setting literature—that EDPs are relevant and feasible within LICs. The extreme lack of resources necessitates making tough decisions which may mean depriving populations of potentially valuable health technologies. It is critical that the decisions and the decision making bodies are perceived as fair and legitimate by the people that are most affected by the decisions. EDPs are well aligned with the political infrastructure in some LICs, which encourages public participation in decision making. Furthermore, many countries are committed to evidence-informed decision making. However, the application of EDPs may be hampered by the limited availability of evidence of good quality, lack of interest in transparency and accountability (in some LICs), limited capacity to conduct HTA, as well as limited time and financial resources to invest in a deliberative process. While EDPs would potentially benefit many LICs, mitigating the identified potential barriers would strengthen their applicability. We believe that implementation studies in LICs, documenting the contextualized enablers and barriers will facilitate the development of context specific improvement strategies for EDPs.